Graphite oxide catalyzed one-pot synthesis of highly functionalized spirodibenzo[1, 4]diazepine derivatives in aqueous ethanol medium. Issue 14 (29th June 2022) - Sarkar, Rajib; Dam, Binoyargha; Kyndiah, Lenida; Sarkar, Fillip Kumar; Gajurel, Sushmita; Pal, Amarta Kumar
Abstract : We presented the synthesis of highly functionalized spirodibenzo[1, 4]diazepine derivatives using graphite oxide (GO) as a metal-free carbocatalyst via a one-pot three-component strategy. Abstract : In this work, graphite oxide (GO) was developed from cheap and readily available graphite powder and used as a green heterogeneous carbocatalyst towards the synthesis of spirodibenzo[1, 4]diazepine derivatives via a one-pot three-component strategy. The reactions were performed under mild conditions in aqueous ethanol medium to obtain diversely functionalized target products. A gram-scale reaction was also performed to demonstrate the scalability and practical applicability of the developed methodology. Moreover, the reusability study of the catalyst has shown that the catalyst can be reused up to eight consecutive cycles without significant loss of its catalytic activity. Operational simplicity, easy workup, high substrate scope, good to high yields and easy recyclability of the catalyst are some of the promising features of the present methodology. Additionally, the use of GO as a metal-free catalyst can avoid the incorporation of metal impurities in the final products.